The genome sequence of the yellow mealworm beetle, Tenebrio molitor Linnaeus, 1758 [version 1; peer review: 2 approved] - Darren Mann; Nilo Merino Recalde; Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from a male yellow mealworm Tenebrio molitor larva (Arthropoda; Insecta; Coleoptera; Tenebrionidae). The genome sequence has a total length of 277.00 megabases. Most of the assembly is scaffolded into 11 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled and is 15.78 kilobases in length.